STUDI KEARIFAN LOKAL SUKU ANAK DALAM LUBUK KAYU ARO DESA PELEMPANG KABUPATEN MUARO JAMBI (ANALISIS DALAM MEMILIH PEMIMPIN (TUMENGGUNG) PADA SUKU ANAK DALAM) - sari, Yulia; Nurhasanah, Andi; Fiqhi, Ajuzar (STKIP Pesisir Selatan, 2026)
The SAD (Sad) has a unique social structure that differs from that of most rural communities. They form small groups led by a traditional leader or informal leader, usually called Tumenggung. The purpose of this study was to determine the traditional leadership structure, the specific criteria for selecting a leader, and the customary process or mechanism for selecting a leader in the Anak Dalam tribe. This research was conducted over a period of approximately two months. The Tumenggung is not simply the head of the group, but also holds customary, legal, social, and cultural authority, recognized collectively by all members of the tribal group. This research method is qualitative. The data collection techniques used were primary data, including field research, an ethnographic approach through participant observation, and in-depth interviews with various sources considered key informants, including both the community and the government as agents of development and documentation. The results of this study indicate that the social structure or strata of the SAD community in Pelempang village is based on a power system, in addition to a system of trust in leaders, in this case the highest leader they call Tumenggung.